GE_GERICHTE P/959/2011 vom 15. März 2013 - GE Cour de justice (2013)
LÉGITIME DÉFENSE; VOIES DE FAIT; INDEMNITÉ(EN GÉNÉRAL); REMBOURSEMENT DE FRAIS(SENS GÉNÉRAL); ACQUITTEMENT | CP.126.1; CP.15; CP.17; CPP.433; CPP.429.1.A; CPP.132.1.B